Epidemiology of fragile X syndrome: A systematic review and meta-analysis - Hunter, J; Rivero-Arias, O; Angelov, A; Kim, E; Fotheringham, I; Leal, J (Wiley-Liss Inc., 2014)
Prevalence estimates for fragile X syndrome vary considerably. This systematic review and meta-analysis was conducted to provide an accurate prevalence estimate for this disorder using primary publications in PubMed, Embase, and the Cochrane library. Data were pooled using Bayesian fixed-effects and random-effects models. Primary analyses assessed the frequency of the full mutation and premutation in males and females in the total population (no bias against individuals with intellectual disability) and in female carriers of the premutation in normal populations (biased against individuals with intellectual disability), based on diagnosis by polymerase chain reaction or Southern blotting. A sensitivity analysis included studies using any diagnostic testing method and conference abstracts. Sixty-eight recorded observations provided data for the primary (56 observations) and sensitivity (12 observations) analysis. Using the random-effects model, frequency of the full mutation was 1.4 (95% CI: 0.1-3.1) per 10,000 males and 0.9 (95% CI: 0.0-2.9) per 10,000 females (1:7,143 and 1:11,111, respectively) in the total population. The premutation frequency was 11.7 (95% CI: 6.0-18.7) per 10,000 males and 34.4 (95% CI: 6.3-83.3) per 10,000 for females (1:855 and 1:291, respectively) in the total population. The prevalence of female carriers of the premutation in the normal population was 34.4 (95% CI: 8.9-60.3) per 10,000, or 1:291. Sensitivity analyses resulted in similar prevalence estimates but with wider heterogeneity. Prevalence estimates for the full mutation from this meta-analysis are lower than those in previous reviews of fragile X syndrome epidemiological data. © 2014 Wiley Periodicals, Inc.